2012
DOI: 10.1103/physrevb.86.195409
|View full text |Cite
|
Sign up to set email alerts
|

Half-metallic ferromagnetism in substitutionally doped boronitrene

Abstract: We perform first principles molecular dynamics simulations to investigate the magnetoelectronic response of substitutionally-doped boronitrene to thermal excitation. We show that the local geometry, size and edge-termination of the substitutional complexes of boron, carbon or nitrogen determine the thermodynamic stability of the monolayer. We find that hexagonal boron or triangular carbon clusters induce finite magnetic moments with 100% spinpolarized Fermi-level electrons in boronitrene. In such carbon substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Some examples of such collective phenomena include formation of Hofstadter's butterfly in graphene/boron nitride (hBN) heterostructures, giant tunneling magnetoresistance in ferromagnet/ vdW multilayers and interlayer coupling of electron-phonon modes in vdW heterostructures [5]. Consider that first principles calculations of the ground state properties of free-standing hBN monolayers show that decoration of the nitrogen vacancyantisite complex with charges [6], and functionalization of the hBN monolayer with substitutional carbon antisite complexes of boron and its surrounding nitrogen atoms (C 1B + C 3N ) [7], induce temperature independent magn etic moments. Though this defect-induced magnetic moment in hBN is not strictly a ferromagnetic state [8], it is shown herein that spin filtering in Fe-hBN/graphene magnetic tunnel junction (MTJ) devices can be used to offer an alternative pathway for quantum information encoding [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of such collective phenomena include formation of Hofstadter's butterfly in graphene/boron nitride (hBN) heterostructures, giant tunneling magnetoresistance in ferromagnet/ vdW multilayers and interlayer coupling of electron-phonon modes in vdW heterostructures [5]. Consider that first principles calculations of the ground state properties of free-standing hBN monolayers show that decoration of the nitrogen vacancyantisite complex with charges [6], and functionalization of the hBN monolayer with substitutional carbon antisite complexes of boron and its surrounding nitrogen atoms (C 1B + C 3N ) [7], induce temperature independent magn etic moments. Though this defect-induced magnetic moment in hBN is not strictly a ferromagnetic state [8], it is shown herein that spin filtering in Fe-hBN/graphene magnetic tunnel junction (MTJ) devices can be used to offer an alternative pathway for quantum information encoding [9].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] These special features make the nonmetal doped h-BN system a potential candidate for spin-based device exploitation (which utilizes the electronic spin states for data storage and processing). The search for suitable Half-MetallicFerromagnet (HMFM) materials started in 1983 after the De Groot et al [22] discovery.…”
Section: Introductionmentioning
confidence: 99%
“…[19,[38][39][40][41] It was reported that the C impurity spontaneously induces magnetization and half-metallic character. [19][20][21][38][39][40][41] Ukpong et al [21] have shown via DFT calculations that the induced magnetic moments are easily affected by the size of the embedded C impurity cluster and edge termination. Berseneva et al [20] reported that the C substitution processes are controlled by the energetics of the atomic configurations, more especially when the system is charged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus adopt the Heisenberg Hamiltonian to interpret the field-induced band magnetism, where J is the magnetic exchange coupling. Here S i denotes the total spin magnetic moment at atomic site i obtained as the vector sum over all the spins of unpaired electrons, with i and j labeling two nearest-neighbor sites [ 63 ].…”
Section: Resultsmentioning
confidence: 99%